Gas barrier laminate and packaging bag
Patent Information
- Application Number
- JP2020165039
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-30
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-09-30
AI Technical Summary
【0014】 本発明によれば、紙の特徴である折り目保持性を有し且つ折り曲げられた後であっても十分なガスバリア性を有するとともに、プラスチック材料の使用量削減に寄与するガスバリア積層体及びこれを含む包装袋を提供することができる。
Smart Images

Figure 0007631721000005 
Figure 0007631721000006 
Figure 0007631721000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a gas barrier laminate and a packaging bag. [Background technology]
[0002] In many fields, such as food, beverages, pharmaceuticals, and chemicals, packaging materials are used according to the contents. Packaging materials are required to have gas barrier properties that prevent the permeation of oxygen and water vapor, which can cause deterioration of the contents.
[0003] In recent years, the momentum for eliminating plastic has been increasing due to growing environmental awareness triggered by the problem of marine plastic waste. From the viewpoint of reducing the amount of plastic materials used, the use of paper instead of plastic materials has been considered in various fields. For example, Patent Document 1 below discloses a gas barrier laminate in which a barrier layer is laminated on paper. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-62973 A Summary of the Invention [Problem to be solved by the invention]
[0005] Paper has the characteristic of being easy to process due to its crease retention (also called dead-hold property). However, according to the study by the present inventors, it was found that there is still room for improvement in that cracks occur in the barrier layer and the gas barrier property is reduced when paper is used for packaging bags with sharper creases (pillow packaging, three-side seal packaging, and gusset packaging).
[0006] Moreover, from the viewpoint of the Law for Promoting Effective Utilization of Resources, it is required to reduce the amount of plastic materials used in gas barrier laminates as well.
[0007] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide a gas barrier laminate that has the crease retention characteristic of paper and sufficient gas barrier properties even after being folded, and that contributes to reducing the amount of plastic materials used, and a packaging bag including the same. [Means for solving the problem]
[0008] The present invention provides a gas barrier laminate comprising, in this order, a paper substrate, a first resin layer, a first vapor deposition layer, a layer containing a polyvinyl alcohol-based resin, a second vapor deposition layer, and a second resin layer.
[0009] The second resin layer may be a layer containing a polyolefin having at least one selected from a carboxyl group, a salt of a carboxyl group, a carboxylic anhydride group, and a carboxylate ester.
[0010] At least one of the first vapor-deposited layer and the second vapor-deposited layer may be an aluminum vapor-deposited layer having a thickness of 30 nm or more and 100 nm or less.
[0011] The thickness of the paper substrate may be 30 μm or more and 100 μm or less, and the thickness of the paper substrate may be 60% or more of the total thickness of the gas barrier laminate.
[0012] The present invention also provides a packaging bag comprising the gas barrier laminate according to the present invention.
[0013] The packaging bag may have a folded portion. Effect of the Invention
[0014] According to the present invention, it is possible to provide a gas barrier laminate and a packaging bag including the same, which have the crease retention characteristic of paper and sufficient gas barrier properties even after being folded, and which contribute to reducing the amount of plastic materials used. [Brief description of the drawings]
[0015] [Figure 1] 1 is a schematic cross-sectional view showing a gas barrier laminate according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a perspective view showing a package according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings as needed. However, the present invention is not limited to the following embodiments.
[0017] <Gas barrier laminate> 1 is a schematic cross-sectional view showing a gas barrier laminate according to one embodiment. The gas barrier laminate 10 according to one embodiment includes a paper substrate 1, a first resin layer 2, a first vapor-deposited layer 3, a layer 4 containing a polyvinyl alcohol-based resin, a second vapor-deposited layer 5, and a second resin layer 6, in this order.
[0018] [Paper base material] The paper substrate 1 is not particularly limited and may be appropriately selected depending on the application of the packaging material to which the gas barrier laminate 10 is applied. Specific examples of the paper substrate 1 include fine paper, special fine paper, coated paper, art paper, cast coated paper, glassine paper, imitation paper, and kraft paper. The thickness of the paper substrate 1 may be, for example, 20 μm or more and 200 μm or less, or 30 μm or more and 100 μm or less. The thickness of the paper substrate may be 60% or more, or 70% or more of the thickness of the entire gas barrier laminate. If the thickness of the paper substrate is 60% or more of the thickness of the entire gas barrier laminate, it can be said that the gas barrier laminate has excellent environmental suitability.
[0019] The paper base material 1 may have a coating layer at least on the side in contact with the first resin layer 2 described below. The coating layer can prevent the first resin layer 2 from soaking into the paper, and can also act as a sealant to fill in the unevenness of the paper, allowing the first resin layer 2 to be formed uniformly without defects. The coating layer may contain, as a binder resin, various copolymers such as styrene-butadiene, styrene-acrylic, and ethylene-vinyl acetate copolymers, polyvinyl alcohol resins, cellulose resins, paraffin (WAX), and the like, and may contain, as a filler, clay, kaolin, calcium carbonate, talc, mica, and the like.
[0020] The thickness of the coating layer is not particularly limited, but may be, for example, from 1 μm to 10 μm, or from 3 μm to 8 μm.
[0021] The weight of the paper is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, based on the weight of the entire gas barrier laminate. If the weight of the paper is 50% by mass or more based on the weight of the entire gas barrier laminate, the amount of plastic material used can be sufficiently reduced, the gas barrier laminate as a whole can be said to be made of paper, and recyclability is excellent.
[0022] [First resin layer] The first resin layer 2 is provided on the surface of the paper substrate to improve adhesion between the paper substrate 1 and the first deposition layer 3 described below, to smooth the surface of the first deposition layer 3, and to prevent cracking of the first deposition layer due to bending. Materials constituting the first resin layer 2 include polyolefin-based emulsions, silane coupling agents, organic titanates, polyacrylics, polyesters, polyurethanes, polycarbonates, polyureas, polyamides, polyimides, melamines, phenols, and polyvinyl alcohol-based resins. Among these, polyolefin-based emulsions are preferred in terms of water vapor barrier properties, bending resistance, and adhesion to the first deposition layer 3.
[0023] From the viewpoint of adhesion to the first deposition layer 3, the polyolefin-based emulsion is preferably a polyolefin having at least one selected from, for example, a carboxyl group, a salt of a carboxyl group, a carboxylic anhydride group, and a carboxylate ester. By including such a polyolefin, a dense film is formed due to hydrogen bonds of the carboxyl group, aggregation due to metal ions of the ionomer, and crystallinity of the polyolefin, and the barrier properties are excellent. Such a first resin layer 2 has excellent flexibility and can suppress cracking of the first deposition layer 3 described below after bending (folding). The smaller the particle size of the polyolefin-based emulsion, the better, and specifically, it may be 1 μm or less, 0.7 μm or less, or 0.5 μm or less. The lower limit of the average particle size of the first polyolefin is not particularly limited, but may be, for example, 1 nm or more. This makes the coating surface smooth after drying, making the deposition surface uniform and ensuring the initial barrier properties.
[0024] The thickness of the first resin layer 2 may be, for example, 1 μm or more and 20 μm or less. If the thickness is 1 μm or more, the unevenness of the paper is filled and the deposition layer can be laminated uniformly. Also, if the thickness is 20 μm or less, costs can be reduced.
[0025] The first resin layer 2 can be provided by applying a coating liquid containing the first resin layer and a solvent onto a paper substrate and drying the coating liquid. Examples of the solvent contained in the coating liquid include water, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, n-pentyl alcohol, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, toluene, hexane, heptane, cyclohexane, acetone, methyl ethyl ketone, diethyl ether, dioxane, tetrahydrofuran, ethyl acetate, and butyl acetate. These solvents may be used alone or in combination of two or more. Among these, from the viewpoint of characteristics, methyl alcohol, ethyl alcohol, isopropyl alcohol, toluene, ethyl acetate, methyl ethyl ketone, and water are preferred. From the viewpoint of environment, methyl alcohol, ethyl alcohol, isopropyl alcohol, and water are preferred. The coating liquid may also contain additives such as surfactants, preservatives, storage stabilizers, silane coupling agents, organic titanates, and defoamers.
[0026] [First deposition layer] The first vapor-deposited layer 3 has a role of imparting water vapor barrier properties and complementing the water vapor barrier properties when the second vapor-deposited layer 5, which will be described later, is broken due to bending, and is a layer formed by vapor-depositing a metal or an inorganic oxide. The first vapor-deposited layer 3 may be obtained by vapor-depositing aluminum, and aluminum oxide (AlO x ), silicon oxide (SiO x ) The first vapor-deposited layer is preferably an aluminum vapor-deposited layer.
[0027] The thickness of the first vapor-deposited layer 3 may be appropriately set depending on the application, but may be preferably 10 nm or more, 30 nm or more, or 50 nm or more, and may be 500 nm or less, 100 nm or less, or 80 nm or less. By setting the thickness of the first vapor-deposited layer 3 to 10 nm or more, the continuity of the first vapor-deposited layer 3 can be easily ensured, and by setting the thickness to 500 nm or less, the occurrence of curling or cracking can be sufficiently suppressed, and sufficient gas barrier performance and flexibility can be easily achieved.
[0028] The first deposition layer 3 is preferably formed by a vacuum deposition means from the viewpoint of oxygen gas barrier performance and film uniformity. There are known deposition means such as vacuum deposition, sputtering, and chemical vapor deposition (CVD), but vacuum deposition is preferred because of its fast deposition rate and high productivity. Among the vacuum deposition methods, deposition means using electron beam heating is particularly effective because the deposition rate can be easily controlled by the irradiation area and electron beam current, and the temperature of the deposition material can be raised and lowered in a short time.
[0029] [Layer containing polyvinyl alcohol resin] The layer 4 containing a polyvinyl alcohol-based resin is provided to improve adhesion between the first vapor-deposited layer 3 and the second vapor-deposited layer 5 described below, to prevent cracking of the first vapor-deposited layer 3 and the second vapor-deposited layer 5 due to bending, or to improve the oxygen barrier properties of the gas barrier laminate.
[0030] In the gas barrier laminate according to this embodiment, when the second resin layer described later is folded on the outside, even if the second vapor-deposition layer is cracked by stretching the second resin layer described later, the presence of layer 4 containing a flexible polyvinyl alcohol-based resin can reduce the risk of cracking the first vapor-deposition layer. Furthermore, in the gas barrier laminate according to this embodiment, when the second resin layer is folded on the inside, even if the first vapor-deposition layer is cracked by stretching the cracks in the first resin layer or coating layer, the presence of layer 4 containing a flexible polyvinyl alcohol-based resin can reduce the risk of cracking the second vapor-deposition layer.
[0031] As the polyvinyl alcohol-based resin, a fully saponified polyvinyl alcohol-based resin, a partially saponified polyvinyl alcohol-based resin, a modified polyvinyl alcohol, an ethylene-vinyl alcohol copolymer resin, etc. can be used. The polymerization degree of these resins is preferably 300 or more and 1500 or less. If the polymerization degree is 300 or more, the barrier properties and bending resistance of the gas barrier laminate become good, and if the polymerization degree is 1500 or less, the viscosity of the coating liquid of the polyvinyl alcohol-based resin described below becomes low, and the coating property becomes good.
[0032] The layer 4 containing the polyvinyl alcohol resin can be provided by applying a coating liquid containing the above-mentioned polyvinyl alcohol resin and a solvent onto the first vapor deposition layer 3 and drying it. Examples of the solvent contained in the coating liquid include water, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, n-pentyl alcohol, dimethyl sulfoxide, dimethylformamide, and dimethylacetamide, and in particular, a mixed solvent of water and an alcohol such as methyl alcohol, ethyl alcohol, or isopropyl alcohol is preferred. The coating liquid may also contain additives such as surfactants, preservatives, storage stabilizers, silane coupling agents, and organic titanates.
[0033] The thickness of the layer 4 containing a polyvinyl alcohol-based resin may be, for example, 0.05 μm or more and 10 μm or less. When the thickness is 0.05 μm or more, the oxygen barrier property is easily improved sufficiently, and when the thickness is 10 μm or less, the cost can be reduced and the ratio of paper in the gas barrier laminate according to this embodiment can be increased.
[0034] [Second deposition layer] The second vapor-deposited layer 5 has a role of imparting water vapor barrier properties and complementing the water vapor barrier properties when the first vapor-deposited layer 3 is cracked due to bending, and is a layer formed by vapor-depositing a metal or an inorganic oxide. The second vapor-deposited layer 5 may be obtained by vapor-depositing aluminum, and aluminum oxide (AlO x ), silicon oxide (SiO x ) The second vapor-deposited layer 5 is preferably an aluminum vapor-deposited layer.
[0035] The thickness of the second vapor-deposited layer 5 may be appropriately set depending on the application, but may be preferably 10 nm or more, 30 nm or more, or 50 nm or more, and may be 500 nm or less, 100 nm or less, or 80 nm or less. By setting the thickness of the second vapor-deposited layer 5 to 10 nm or more, the continuity of the second vapor-deposited layer 5 can be easily ensured, and by setting the thickness to 500 nm or less, the occurrence of curling or cracking can be sufficiently suppressed, and sufficient gas barrier performance and flexibility can be easily achieved.
[0036] The second deposition layer 5 is preferably formed by a vacuum deposition means from the viewpoint of oxygen gas barrier performance and film uniformity. There are known deposition means such as vacuum deposition, sputtering, and chemical vapor deposition (CVD), but vacuum deposition is preferred because of its high deposition rate and high productivity. Among the vacuum deposition methods, deposition means using electron beam heating is particularly effective because the deposition rate can be easily controlled by the irradiation area and electron beam current, and the temperature of the deposition material can be raised and lowered in a short time.
[0037] [Second resin layer] The second resin layer 6 improves adhesion to the second vapor-deposited layer 5 and prevents the second vapor-deposited layer 5 from cracking due to bending, and can also impart heat sealability to the second resin layer 6.
[0038] The material constituting the second resin layer 6 may be a layer containing a polyolefin having at least one selected from a carboxyl group, a salt of a carboxyl group, a carboxylic anhydride group, and a carboxylic acid ester. The second resin layer 6 is preferably an aqueous emulsion, and preferably contains a polyolefin emulsion having at least one selected from a carboxyl group, a salt of a carboxyl group, a carboxylic anhydride group, and a carboxylic acid ester. Polyolefins have excellent flexibility and can suppress vapor deposition cracks after bending, and the crystallinity of polyolefins provides excellent water vapor barrier properties.
[0039] The second resin layer 6 can be provided by applying a coating liquid containing a resin and a solvent constituting the second resin layer on the second deposition layer and drying the coating liquid. Examples of the solvent contained in the coating liquid include water, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, n-pentyl alcohol, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, toluene, hexane, heptane, cyclohexane, acetone, methyl ethyl ketone, diethyl ether, dioxane, tetrahydrofuran, ethyl acetate, and butyl acetate. These solvents may be used alone or in combination of two or more. Among these, from the viewpoint of characteristics, methyl alcohol, ethyl alcohol, isopropyl alcohol, toluene, ethyl acetate, methyl ethyl ketone, and water are preferred. From the viewpoint of environment, methyl alcohol, ethyl alcohol, isopropyl alcohol, and water are preferred. The coating liquid may also contain additives such as surfactants, preservatives, storage stabilizers, silane coupling agents, organic titanates, antifoaming agents, and blocking inhibitors.
[0040] The film thickness of the second resin layer 6 may be 0.05 μm or more and 20 μm or less, 0.5 μm or more and 10 μm or less, or 1 μm or more and 5 μm or less.
[0041] <Oxygen permeability, water vapor permeability> The gas barrier laminate according to this embodiment can exhibit sufficient gas barrier properties even after being folded. In this specification, gas barrier properties means that the water vapor permeability and oxygen permeability are sufficiently low.
[0042] The water vapor permeability of the gas barrier laminate according to this embodiment is, when measured by the MOCON method, 2 g / m at a temperature of 40° C. and a relative humidity of 90% RH. 2 ·days or less is preferable.
[0043] The oxygen permeability of the gas barrier laminate according to this embodiment is, when measured according to JIS K7126, Method B (isobaric method), at a temperature of 30° C. and a relative humidity of 70% RH, 2 cc / m 2 It is preferable that the concentration is / d / atm or less.
[0044] The gas barrier laminate according to this embodiment has the second resin layer 6 side facing inward. When a roller weighing 1500 g is rolled once over the gas barrier laminate and the fold is opened to measure the water vapor permeability and oxygen permeability, the water vapor permeability is 3 g / m at a temperature of 40° C. and a relative humidity of 90% RH. 2 ·day or less, and the oxygen permeability is 3cc / m2 or less at a temperature of 30°C and a relative humidity of 70%RH. 2 It is preferable that the concentration is / d / atm or less.
[0045] In the gas barrier laminate according to this embodiment, the second resin layer 6 is placed on the outside. When a roller weighing 1500 g is rolled once over the gas barrier laminate and the fold is opened to measure the water vapor permeability and oxygen permeability, the water vapor permeability is 3 g / m at a temperature of 40° C. and a relative humidity of 90% RH. 2 ·day or less, and the oxygen permeability is 3cc / m2 or less at a temperature of 30°C and a relative humidity of 70%RH. 2 It is preferable that the concentration is / d / atm or less.
[0046] <Packaging bag> 2 is a perspective view showing a gusset bag 20 made of a gas barrier laminate 10. A packaging bag is produced by sealing the opening at the top of the gusset bag 20. The gusset bag 20 has portions where the gas barrier laminate 10 is folded (folded portions B1, B2). The folded portion B1 is a portion where the gas barrier laminate is folded in a valley when viewed from the innermost layer side, while the folded portion B2 is a portion where the gas barrier laminate 10 is folded in a mountain when viewed from the innermost layer side.
[0047] The packaging bag may be formed into a bag shape by folding one gas barrier laminate in half so that the second resin layers 6 face each other, then folding appropriately into a desired shape and heat sealing, or may be formed into a bag shape by stacking two gas barrier laminates so that the second resin layers 6 face each other, and then heat sealing.
[0048] In the packaging bag according to the present embodiment, the heat seal strength may be 2 N or more, or 4 N or more. The upper limit of the heat seal strength is not particularly limited, but may be, for example, 10 N or less.
[0049] The packaging bag can contain food, medicine, and the like. It is particularly suitable for containing food, such as sweets. The packaging bag according to the present embodiment can maintain high gas barrier properties even in a shape having a folded portion.
[0050] In this embodiment, a gusset bag is given as an example of a packaging bag, but the gas barrier laminate according to this embodiment may be used to produce, for example, a pillow bag, a three-side sealed bag, or a standing pouch. EXAMPLES
[0051] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0052] <Preparation of gas barrier laminate> (Examples 1 to 9, Comparative Examples 1 to 5) A gas barrier laminate was obtained by forming a first resin layer, a first vapor deposition layer, a layer containing a polyvinyl alcohol resin, a second vapor deposition layer, and a second resin layer on the clay-coated surface of paper (clay-coated paper, paper thickness: 50 μm, clay-coated layer thickness: 5 μm) as shown in Tables 1 to 4 below. The materials used are as follows:
[0053] Chemipearl S100: A solution containing a salt of a carboxyl group (manufactured by Mitsui Chemicals) Chemipearl S500: A solution containing a salt of a carboxyl group (manufactured by Mitsui Chemicals) Chemipearl V300: A coating solution containing vinyl acetate polyolefin resin (manufactured by Mitsui Chemicals)
[0054] <Measurement of water vapor permeability> The water vapor permeability of the gas barrier laminates according to the examples and comparative examples was measured by the MOCON method. The measurement conditions were a temperature of 40°C and a relative humidity of 90%. The gas barrier laminate was creased while a 1500g roller was rotated once at a speed of 300mm / min, and the water vapor permeability of the gas barrier laminate after opening was also measured in the same manner. In Tables 1 to 4, "valley fold" refers to the gas barrier laminate after the gas barrier laminate has been valley folded as viewed from the paper substrate side, and "mountain fold" refers to the gas barrier laminate after the gas barrier laminate has been mountain folded as viewed from the paper substrate side. The results are shown in Tables 1 to 4 in the unit [g / m 2 ·day].
[0055] <Oxygen permeability measurement> The oxygen permeability of the gas barrier laminates according to the examples and comparative examples was measured according to JIS K7126, method B (isobaric method). The measurement was performed using an OXTRAN 2 / 20 made by MOCON at a temperature of 30° C. and a relative humidity of 70%. The results are shown in Tables 1 to 4 in units of [cc / m 2 The folding method was the same as for the water vapor transmission rate.
[0056] <Heat seal strength measurement> Two gas barrier laminates were stacked with the paper substrate facing outward, and heat sealed with a heat sealer at 120°C, 0.2 MPa, and 1 second, and then cut into 15 mm wide strips and measured for maximum load when T-peeled at a peel speed of 300 mm / min. The results are shown in Tables 1 to 4 in units of [N / 15 mm].
[0057] [Table 1]
[0058] [Table 2]
[0059] [Table 3]
[0060] [Table 4] [Explanation of symbols]
[0061] 1...paper base material, 2...first resin layer, 3...first vapor deposition layer, 4...layer containing polyvinyl alcohol-based resin, 5...second vapor deposition layer, 6...second resin layer, 10...gas barrier laminate, 20...gusset bag, B1, B2...folded portion.
Claims
1. A gas barrier laminate comprising, in this order, a paper substrate, a first resin layer, a first vapor deposition layer, a layer containing a polyvinyl alcohol-based resin, a second vapor deposition layer, and a second resin layer, the first resin layer contains a polyolefin having at least one selected from a carboxyl group, a salt of a carboxyl group, a carboxylic anhydride group, and a carboxylic acid ester; the second resin layer contains a polyolefin having at least one selected from a carboxyl group, a salt of a carboxyl group, a carboxylic anhydride group, and a carboxylic acid ester; A gas barrier laminate, wherein the first vapor-deposited layer is an aluminum vapor-deposited layer (however, this excludes gas barrier laminates in which the first resin layer contains a melamine resin, an alkyd resin, a polyphenol resin or an acrylic resin).
2. A gas barrier laminate comprising, in this order, a paper substrate, a first resin layer, a first vapor deposition layer, a layer consisting only of a polyvinyl alcohol-based resin, a second vapor deposition layer, and a second resin layer, the first resin layer is a layer made only of a polyvinyl alcohol-based resin, the second resin layer contains a polyolefin having at least one selected from a carboxyl group, a salt of a carboxyl group, a carboxylic anhydride group, and a carboxylic acid ester; The gas barrier laminate, wherein the first vapor-deposited layer is an aluminum vapor-deposited layer.
3. The gas barrier laminate according to claim 1 or 2, wherein the second vapor-deposited layer is an aluminum vapor-deposited layer.
4. The gas barrier laminate according to any one of claims 1 to 3, wherein the first vapor-deposited layer and the second vapor-deposited layer each have a thickness of 30 nm or more and 100 nm or less.
5. 5. The gas barrier laminate according to claim 1, wherein the thickness of the paper base material is 30 μm or more and 100 μm or less, and the thickness of the paper base material is 60% or more of the total thickness of the gas barrier laminate.
6. The gas barrier laminate according to any one of claims 1 to 5, wherein the first resin layer is a single layer, the first resin layer is in direct contact with the paper base material, and the first resin layer is in direct contact with the first vapor deposition layer.
7. A packaging bag comprising the gas barrier laminate according to any one of claims 1 to 6.
8. The packaging bag according to claim 7, having a folded portion.
Citation Information
Patent Citations
Cylindrical paper container
JP1998139032A
Moisture-proof paper and packaging paper, packaging bag or paper container using the same
JP2004204366A
Pressure-sensitive adhesive film having high gas barrier properties
JP2004276294A
Gas barrier film and its manufacturing method
JP2007098676A
Barrier film for a paper container, laminate material for a paper container consisting of the same, and paper liquid container
JP2014141014A